GENDER EQUITY IN INDIGENOUS SOCIETIES: EMPOWERING WOMEN IN NORTHEAST INDIA - Konwar, Bijaya (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Indigenous women in Northeast India, particularly from communities such as the Khasi, Garo, and Jaintia, play a pivotal role in preserving cultural heritage, sustaining economic activities, and fostering community resilience, yet they face significant gender-specific challenges, including economic marginalization, health disparities, political exclusion, and gender-based violence. This article explores the historical and contemporary roles of indigenous women, emphasizing their contributions to cultural preservation, economic stability, and community governance within matrilineal frameworks. It examines the impact of colonial legacies, globalization, and modernization on gender dynamics, highlighting systemic barriers that perpetuate inequality. To address these challenges, the article advocates for culturally sensitive gender equity initiatives, including enhanced access to education, economic resources, healthcare, political participation, and robust legal protections against violence. By fostering empowerment through targeted interventions such as vocational training, micro-financing, reproductive health programs, and leadership development, these initiatives aim to strengthen the agency of indigenous women, ensuring their voices shape policy and decision-making. The study underscores that empowering indigenous women not only promotes gender equity but also drives sustainable development, reinforcing the socio-cultural and economic fabric of their communities in Northeast India. This study is based on secondary source of data and follows an analytical method